'Our Fellow Shakespeare': A Contemporary Classic in the Early Modern University. (25th January 2020) - Blank, Daniel
Abstract: This essay discusses the reception of Shakespeare's works among the students and fellows of early modern Oxford and Cambridge. Taken at face value, the documentary record would seem to suggest that Shakespeare had no place there, as authorities at the two English universities aimed to prevent the presence of his work in the academic sphere. However, this essay uses a variety of literary and archival evidence to show that Shakespeare's works not only entered into scholarly discourse, but also achieved a status that had previously been reserved for ancient authors. I argue that the best window into Shakespeare's reception among early modern scholars can be found in academic drama, and I examine two university theatrical productions that engage closely with his works: the Parnassus plays, performed at Cambridge between 1598 and 1601, and Narcissus, performed at Oxford in 1602. These plays not only provide early examples of Shakespeare's reception among intellectuals, but also illustrate how the scholars of Oxford and Cambridge figured Shakespeare as a 'classical' author—an author as worthy of imitation as Homer or Ovid. The process of establishing Shakespeare as a 'classic' in the academic setting, this essay ultimately argues, began much earlier than scholars have realized.